PENGARUH LAYANAN INFORMASI TENTANG STUDI LANJUT TERHADAP PERENCANAAN KARIR SISWA KELAS XI IPA SMA NEGERI 1 PEKANBARU TAHUN AJARAN 2013/2014 - Liza, Ledya Oktavia; Yakub, Elni; Arlizon, Raja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research aims to; 1) To know the description of career planning ofstudenst before being given information service about further studies. 2) To know thedescription of career planning of students after given information service about furtherstudies. 3) To figure out the difference in career planning of students before and aftergiven information service about further studies. 4) To know how the effect ofinformation service about further studies on career planing of students. The methodused is Quasi experiment method, using One group pretest-postest design. Thepopulation of this research is students of class XI Science SMA Negeri 1 Pekanbaru andsample is 50% of the population, using simple random sampling technique. Based onthe results of data processing the career planning of students before given informationservice about further studies are mostly located in medium category, while after giveninformation service about career planning further studies students are mostly located ongood and very well category. The calculation of test-t obtained t-count greater than ttable(20,9 > 1,960) then the hypothesis is accepted, there is a significant differencebetween career planning of students of class XI Science SMA Negeri 1 Pekanbaruservice performed before and after information about further studies on 5% error level.Based on results of calculation of coefficient of determinant and correlation, then thecontributions information service abou further studies of career planning is 38% whilethe others 62% is affected by other variabels.Keywords: information services, career planning